Enhanced antimicrobial activity of peptide‐cocktails against common bacterial contaminants of ex vivo stored platelets. (9th August 2013) - Mohan, K. V. K.; Rao, S. Sainath; Gao, Y.; Atreya, C. D.; Grobusch, M.
Abstract Bacterial contamination of blood components such as ex vivo‐stored platelets is a major safety risk in transfusion medicine. We have recently shown that synthetic antimicrobial peptides named PD1–PD4 derived from the thrombin‐induced human platelet‐derived antimicrobial proteins, and repeats of Arg‐Trp (RW1–RW5) demonstrate microbicidal activity against selected bacteria and viruses. In the present study, we selected PD3, PD4, RW2, RW3 and RW4 and evaluated each individual peptide and their various combinations to see whether the cocktail regimen enhances the antimicrobial activity above and over the individual peptides. Stored platelet or plasma samples spiked with known titres of Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae and Bacillus cereus were treated with either individual peptides or with peptides in various combinations. Analyses revealed that individual peptides show moderate microbicidal activity (10‐ to 100‐fold reduction) against the tested bacteria relative to their combined regimen. The peptide combinations (RW2 + RW4, RW2 + RW3 + RW4 and PD4 + RW3 + RW4) on the other hand enhanced the microbicidal activity (c.10 000‐fold reduction) and revealed a minimal inhibitory concentration of 5 μM. Time‐kill kinetics indicated that these three peptide combinations exhibited enhanced antimicrobial activity bringing about a 100‐fold reduction of bacterial titres within 20 min of incubation. The present study therefore demonstrates the synergistic effect of antimicrobial peptides when used in combinations and provides a proof‐of‐concept of its potential application as a molecular tool towards pathogen reduction and further extends the possibility of using peptide combinatorial therapeutics as broad‐spectrum antibiotics or as alternatives to combat drug‐resistant bacteria.